(untitled) - Badaracco, Joseph (Boston, Mass., 1991)
Why do successful companies let down their corporate walls, exposing their organizations and strategies to competitors? The answer, according to Joseph Badaracco is that corporations enter into strategic alliances to capitalize on knowledge: migratory knowledge, often technical in nature, which can be transferred easily between people or organizations in a formula or product, and embedded knowledge, which defines how a particular company organizes itself to do business. In today's business environment companies need to utilize each type of knowledge to sustain their competitive advantage. The challenge for today's manager is to balance the opportunities offered by open boundaries and free flowing information against the need to protect the corporations's unique advantages. Managing strategic alliances effectively will determine corporate success in the years ahead.
Keywords: Liên doanh chiến lược (kinh doanh),Strategic alliances (business)